Improving Academic Culture Through MBKM-Based Curriculum Construction at Islamic Higher Education Institution - Syaifuddin, Mohammad; Sopiah, Sopiah; Annur, Aan Fadia; Prayogi, Arditya; Alias, Norma (Program Studi Pendidikan Agama Islam, 2025)
Every university needs to harmonize and reconstruct its curriculum in accordance with national policies to improve the quality of its academic culture. Likewise, UIN K.H. Abdurrahman Wahid Pekalongan must apply the pillars of independent campus learning (MBKM) in its curriculum development. This study aims to explain the curriculum development policy, MBKM-based curriculum construction model, and its problems at UIN K.H. Abdurrahman Wahid Pekalongan. A qualitative field research approach through interviews, observations and documents is used in extracting research data. The results of this study are: 1) MBKM-based curriculum development at UIN K.H. Abdurrahman Wahid Pekalongan is based on the Rector's Decree as a derivative of the Ministry of Education and Culture and Ministry of Religious Affairs policies; 2) The curriculum construction model is characterized by textualist and substantive through the implementation of several MBKM pillars 3) Problems arisen in MBKM-based curriculum construction are related to the determination of courses to be converted, the distribution of courses that are less aligned with MBKM, the financial limitations of students, and the limited availability of MoUs with various related agencies. This research contributes to Islamic education science by offering a context-specific model for integrating MBKM with Islamic values, such as religious moderation, addressing a gap in its application within Islamic higher education. Its long-term implications include informing curriculum frameworks that balance the national policies with the institutional identity, enhancing graduate competencies, and fostering sustainable academic quality in Islamic universities in the MBKM era.